The Analysis of Mangrove Community Ecological Index at the Coastal Area of Pangkalpinang City - Akhrianti, Irma; Gustomi, Andi (Jurnal Ilmiah Platax, 2021)
This research was conducted in the coastal area of Pangkalpinang, Bangka Belitung Province which has an area of 89.4 km2 with a coastline of 36 km2 and is overgrown by mangrove communities that tend to be varied. The research aims to know mangrove community structure at the coastal Pangkalpinang City. This study uses a survey method consisting of 5 observation stations. Mangrove community data were collected using purposive sampling and line transect plot (LTP) methods; 30 m. Data analysis used was an ecological index consisting of a diversity index (Shannon Wienner), a uniformity index (Evenness), and a dominance index (Simpsons). The results showed that 22 species of mangroves were found in the coastal area of Pangkalpinang City, consisting of true mangroves (major and minor) and 2 species of associated mangroves. The type of Analysis of mangrove community structure includes diversity and evenness index at station 5 compared to other stations.  However, the dominance index at station 5 was higher compared to the other stations, which was almost close to 1. Where the mangrove population of each type was not the same and there was a tendency for the population to be dominated by one type of mangrove.Keywords: Diversity; Dominance; Unformity;  Pangkapinang AbstrakPenelitian ini dilakukan di Wilayah Pesisir Kota Pangkalpinang, Provinsi Kepulauan Bangka Belitung. Pangkalpinang merupakan ibukota propinsi Kepulauan Bangka Belitung yang memiliki area sebesar 89.4 km2 dengan panjang garis pantai 36 km2 dan banyak ditumbuhi oleh komunitas mangrove yang cukup bervariasi. Penelitian ini bertujuan untuk mengetahui struktur komunitas mangrove di wilayah pesisir Kota Pangkalpinang. Penelitian ini menggunakan metode survey yang terdiri dari 5 stasiun pengamatan. Pengampilan data komunitas mangrove yaitu dengan menggunakan metode purposive sampling dan line transect plot (LTP) sepanjang 30 meter. Analisis data yang digunakan adalah indeks ekologi yang terdiri dari indeks keanekatagaman (Shannon Wienner) , indeks keseragaman (Eveness), dan indeks dominansi (Simpsons). Hasil penelitian menunjukkan bahwa ditemukan 22 jenis mangrove di wilayah pesisir Kota Pangkalpinang yang terdiri dari mangrove sejati (mayor dan minor) serta 2 spesies dari mangrove asosiasi. Jenis mangrove yang memiliki kelimpahan jenis tertinggi di 5 lokasi penelitian adalah famili Rhizophoraceae. Analisis struktur komunitas mangrove yang meliputi keanekaragaman dan indeks kemerataan pada stasiun 5 dibandingkan stasiun lainnya. Namun indeks dominasi pada stasiun 5 lebih tinggi dibandingkan stasiun lainnya yang hampir mendekati 1. Dimana populasi mangrove masing-masing jenis tidak sama dan terdapat kecenderungan populasi didominasi oleh satu jenis mangrove. Kata kunci:    Dominansi; Keanekaragaman;  Keseragaman; Pangkalpinang